Między polityka a etyką: uwagi o dyskursach politycznej poprawności. Dwugłos krytyczny - Kadir, Djelal; Jędrzejko, Paweł (Er(r)go. Teoria - Literatura - Kultura, 2005)
Djelal Kadir & Paweł Jędrzejko Between Self and State: on Discourses of Political Correctness. A Dialog The central issue of the present dialog is the ambivalence of the phenomenon of „political correctness”. Located in the liminal space between the political discourse of the state and the ethical discourse of individual choices, political correctness, originally postulated as a means to inflect political debates with a modicum of civility, has since morphed into a discursive construct of many faces. In certain contexts, the central concept of the present debate manifests its nature as an obvious tool of power, or becomes a label connoting political or social hypocrisy. At the same time, however, the deliberate application of the now-negative term frequently serves the purpose of disqualifying behaviors, gestures or discourses that are ethically sound, but„inconveniently” reveal the logic of the speaker’s agenda, imperil his/her goals, or deconstruct the elementary distinctions upon which his/her discourse relies. Thus, the dynamics of the present dia-logos of „political correctness” not only indicates that central to the understanding of the amorphous character of the concept is the awareness of the purposes to which its applications may cater, but also, perhaps more importantly, it provides a stimulus for further debates concerning ethics in the context of dominant metanarratives marginalizing other, possibly „discomforting”, discourses.